ROLE OF COMBINED THERAPY IN THE TREATMENT OF PATIENTS WITH INFERTILITY AND REPRODUCTIVE FAILURES - E. V. Vartanyan; E. A. Devyatova; K. A. Tsaturova; D. R. Aglyamova (IRBIS LLC, 2018)
Introduction. Inflammatory gynecological disease is among the major causes of recurrent implantation failures (RIF). In hysteroscopy, chronic endometritis (CE) is diagnosed in one of three women with reproductive dysfunction. Search for novel therapeutic strategies aimed at improving the endometrium condition to overcome the RIF, remains an important goal of reproductive medicine.Aims of the study: 1) identify clinical markers of infertility and RIF; 2) characterize the structural and functional changes in the endometrium of women with infertility and RIF; 3) test the efficacy of the proposed combined therapy in correcting of «uterine factor» of infertility in women with previous in vitro fertilization (IVF) failures.Materials and methods. This cohort retrospective study included 154 patients: Group 1 - 87 women with the tubal factor of infertility; Group 2 - 67 women with adenomyosis. The inclusion criteria: age < 45, ≥ 2 previous IVF failures, the absence of severe non-gynecological disease. After detailed clinical and laboratory examination, we initiated a series of measures for endometrial rehabilitation by using: non-steroid anti-inflammatory drugs (if indicated); tissue regeneration (physiotherapy); immune modulators; improvement of blood rheology; fibrinolytic medication (conjugated hyaluronidase «Longidase», Petrovax Pharm, Russia).Results. In women with the tubal factor of infertility, CE was diagnosed significantly more often (р < 0.05) than in patients with adenomyosis; and in women with adenomyosis, the prevalent (compared to CE) diagnoses were endometrial hyperplasia, intrauterine synechiae and decreased uterine perfusion (р < 0.05). In CE, under-expression of estrogen and progesterone receptors of the endometrium was found in 56.5% cases - significantly more often (р < 0.05) than in patients with adenomyosis. Upon the completion of the proposed therapy, the endometrium thickness was significantly greater in patients with adenomyosis (7.6 ± 1.5 mm versus 11.1 ± 1.3 mm; р < 0.05); in 93.1% of the patients, the sex hormone receptors were restored; in 96.8% of these women, normal uterine perfusion was found. Clinical and morphological signs of CE disappeared in 50% of the treated patients. In this group, the pregnancy rate was 57.1%.Conclusion. Morphologic and functional improvements of the endometrium increase the pregnancy rate in women with the «uterine factor» of infertility. We consider the administration of conjugated hyaluronidase «Longidase» a major factor of the proposed combined therapy. The drug is characterized by fibrinolytic and anti-inflammatory activities. This combined therapeutic approach is expected to contribute to the treatment of RIF.